Bowling alone, policing together - Klinenberg, Eric (Social justice, 2001)
The policing system of the Chicago Alternative Policing Strategy, the most elaborate and extensive community policing program in the U.S., has become an international model for city governments that are interested in reform. The Chicago government has encouraged cooperation in the program by creating a service priority system for residents who form ties with police officers. Requests for city services, such as towing cars, removing graffiti, demolishing abandoned buildings, and repairing broken street signals, receive special treatment when they come via the police department.